A Study on the Performance of In-vitro and In-vivo Germination of Propagatory Materials of Certain Medicinal Plants - Tiwari, R. K. S.; Ojha, B. M.; Shambharkar, Vishal B.; Singh, Vinay; Rajput, M. L. (Indian Forester, 2007)
In-vitro and in-vivo experiments were undertaken conducted to determine the germination of medicinal plant species through seeds and sprouting of cuttings. Seeds of 42 medicinal plant species prevalent in Chhattisgarh forests were selected for germination test in the laboratory as well as in the nursery. For vegetative propagation through cuttings, 44 species were selected. Out of 42 species tested, seed germination was above 90 per cent in species like Aparajita (Clitoria ternatea), Hinglaj (Cassia alata), Jungli sem (Canavalia gladiata), Kasoundhi (Cassia occidentalis), Kenwach (Mucuna pruriens), Ram tulsi (Ocimum basilicum) and Vansuran (Amorphophallus sylvalicus). Whereas, seeds of species i.e. Bharangi (Clerodendrum serratum), Vaividang (Embelia tsjeriam) and Malkangni (Celastrus peniculatus) did not germinate either in the laboratory or in the nursery. Per cent sprouting and survival of the plants from stem cuttings were highest in Hanumansand (Lippia javanica) followed by Gandh prasarni (Paederia foetida), Chitawar (Baliospermum montanum) and Gudmar (Gymnena sylvestre).